Basketball game-related statistics that discriminate between teams' season-long success - Ibanez, S. J.; Sampaio, J.; Feu, S.; Lorenzo, A.; Gomez, M. A.; Ortega, E. (European Journal of Sport Science, 2008)
The aim of the present study was to identify the game-related statistics that discriminate between season-long successful and unsuccessful basketball teams participating in the Spanish Basketball League (LEB1). The sample included all 145 average records per season from the 870 games played between the 2000-2001 and the 2005-2006 regular seasons. The following game-related statistics were gathered from the official box scores of the Spanish Basketball Federation: 2- and 3-point field-goal attempts (both successful and unsuccessful), free-throws (both successful and unsuccessful), defensive and offensive rebounds, assists, steals, turnovers, blocks (both made and received), and fouls (both committed and received). To control for season variability, all results were normalized to minutes played each season and then converted to z-scores. The results allowed discrimination between best and worst teams' performances through the following game-related statistics: assists (SC=0.47), steals (SC=0.34), and blocks (SC=0.30). The function obtained correctly classified 82.4% of the cases. In conclusion, season-long performance may be supported by players' and teams' passing skills and defensive preparation.